The influence of job security on job performance among Jordanian nurses - Raghad Al-Harazneh; Ghada M. Abu shosha; Islam Ali Al-Oweidat; Abdulqadir J. Nashwan (International Journal of Africa Nursing Sciences, 2024)
Background: Job security is one of the basic needs of nurses and it has a great influence on their willingness to work. The effectiveness of job performance of nurses will reflect on the whole organization’s performance by providing high quality health services. Aim: The purpose of this study is to investigate the relationship between job security and employee performance among Jordanian nurses. Method: The study utilized a descriptive, comparative cross-sectional design. It was conducted in two governmental and two private hospitals. A sample of 156 nurses was recruited conveniently to participate in the study. The Job security questionnaire and The Six-Dimension Scale of Nursing Performance were used to collect data. Results: The mean value of the job security score was (3.26) which reflect a moderate level of job security. The employee performance score average was (2.68) reflecting a high level of job performance. There is a significant moderate positive relationship between job security and employee performance (r = 0.404, p < 0.01). Years of experience as a registered nurse (r = −0.18, p < 0.05), years of experience in the current hospital (r = −0.20, p < 0.05), and years of experience in the current unit (r = −0.19, p < 0.05) had a weak negative but significant relationship with employee performance. Conclusion: Nurses with moderate levels of job security obtained high scores on job performance. Future research can look into the characteristics of Jordanian nursing work environments that might have contributed to the observed differences between job security and employee performance.